2016
DOI: 10.1016/j.tins.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Calpain-1 and Calpain-2: The Yin and Yang of Synaptic Plasticity and Neurodegeneration

Abstract: Many signaling pathways participate in both synaptic plasticity and neuronal degeneration. While calpains participate in these phenomena, very few studies have evaluated the respective roles of the two major calpain isoforms in the brain, calpain-1 and calpain-2. We review recent studies indicating that calpain-1 and calpain-2 exhibit opposite functions in both synaptic plasticity and neurodegeneration. Calpain-1 activation is required for the induction of long-term potentiation (LTP) and is generally neuropro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
177
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(192 citation statements)
references
References 88 publications
(93 reference statements)
13
177
1
1
Order By: Relevance
“…Members of the calpain family, however, have different targets and their activation results in a complex array of protein degradation with calpain 1 activation having predominantly neuroprotective effects whilst calpain 2 activation is neurotoxic [68,69]. These calpains may be activated to different degrees in different neuronal subtypes, perhaps explaining patterns of neuronal death in status epilepticus [69].…”
Section: Enzymes Activated By Intracellular Calcium Accumulationmentioning
confidence: 99%
“…Members of the calpain family, however, have different targets and their activation results in a complex array of protein degradation with calpain 1 activation having predominantly neuroprotective effects whilst calpain 2 activation is neurotoxic [68,69]. These calpains may be activated to different degrees in different neuronal subtypes, perhaps explaining patterns of neuronal death in status epilepticus [69].…”
Section: Enzymes Activated By Intracellular Calcium Accumulationmentioning
confidence: 99%
“…However, we found that calpain activity was required 6 h after training to maintain LTM at 24 h. As protein synthesis is not required during this time frame for 24 h LFI memory (Levitan et al, 2010), we hypothesize that calpain activity 6 h post-training targets cytoskeletal proteins permitting synaptic expansion or the growth of new synapses. In mammals, dendritic proteins involved in actin cytoskeletal dynamics including spectrin, RhoA, Drebin, MARCSK are cleaved by calpains facilitating rearrangement of actin cytoskeleton networks and permitting synaptic growth (Baudry and Bi, 2016; Baudry et al, 2011; Baudry et al, 2013). Although long-term memory storage and synaptic growth may be dissociated as recently shown in Aplysia (Chen et al, 2014), synaptic remodeling and the growth of new synapses is considered an integral part of long-term memory stability (Bailey and Kandel, 2008; Kandel, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…At least 14 calpain isoforms and multiple splice variants have been identified in humans (Doshi and Lynch, 2009; Franco and Huttenlocher, 2005; Paquet-Durand et al, 2007; Suzuki et al, 2004; Ueyama et al, 1998; Wu and Lynch, 2006) with calpain-1 and calpain-2 the primary isoforms found in neurons (Baudry and Bi, 2016; Baudry et al, 2013; Briz and Baudry, 2016). Calpain-1 is more sensitive to calcium with in vitro activation occurring at micromolar concentrations while calpain-2 requires near millimolar concentrations of calcium for activation (Baudry and Bi, 2016; Jourdi, 2014). The role of calpains in memory was suggested more than three decades ago with neuronal calpain activity postulated as critical in translating post-synaptic calcium into long-term synaptic changes following the induction of long-term potentiation (Lynch and Baudry, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had indicated that PHLPP1 was truncated during learning, while its overexpression impaired learning, which was interpreted in the context of impairment of ERK activation under this condition (Shimizu et al 2007;Wang et al 2014;Baudry and Bi 2016). It was therefore predicted that PHLPP1 deletion would facilitate LTP induction and learning and memory.…”
Section: Discussionmentioning
confidence: 99%